Qwen2-VL Robustness to Visual Noise in GSM8K-V Benchmarking Against LLaVA-1.6 and InternVL - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 3 peer-reviewed papers addressing the following research question: How does Qwen2-VL's accuracy on GSM8K-V compare to LLaVA-1.6 and InternVL when evaluating robustness to visual noise in grade school math problems. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 0.2/10. This report is a machine-generated literature synthesis and does
Machine-generated literature synthesis.